2019
DOI: 10.1136/jnnp-2018-319318
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of neuroablation and deep brain stimulation for treatment-resistant obsessive-compulsive disorder: a meta-analytic study

Abstract: BackgroundThe safety and efficacy of neuroablation (ABL) and deep brain stimulation (DBS) for treatment refractory obsessive-compulsive disorder (OCD) has not been examined. This study sought to generate a definitive comparative effectiveness model of these therapies.MethodsA EMBASE/PubMed search of English-language, peer-reviewed articles reporting ABL and DBS for OCD was performed in January 2018. Change in quality of life (QOL) was quantified based on the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 36 publications
0
45
1
Order By: Relevance
“…Conversely, DBS is intended to be non-ablative, adjustable in case of side effects of overstimulation and reversible. Current guidelines and meta-analyses do not favor DBS over lesion surgery in the treatment of OCD 33,93. To our opinion, each method presents pros and cons, future researches should focus on identifying predictors of response.…”
Section: Dbs or Lesion Surgery For Ocd?mentioning
confidence: 85%
“…Conversely, DBS is intended to be non-ablative, adjustable in case of side effects of overstimulation and reversible. Current guidelines and meta-analyses do not favor DBS over lesion surgery in the treatment of OCD 33,93. To our opinion, each method presents pros and cons, future researches should focus on identifying predictors of response.…”
Section: Dbs or Lesion Surgery For Ocd?mentioning
confidence: 85%
“…As mentioned above, we previously generated a decision-making analytical model to estimate and compare utility and complication rates of DBS and ABL for treatment-refractory OCD (Kumar et al, 2019). In this model, utility is a measure of relative patient preference for a given healthcare outcome (Weinstein et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…The mean response of Y-BOCS to RF capsulotomy was determined using random-effects and inverse variance-weighted meta-analysis of published observational data including mean age, sex distribution, duration of symptoms, and incidences of individual complications (Einarson, 1997; Nyman et al, 2001; Brown et al, 2016). Using meta-regression of studies measuring both changes in Y-BOCS and QOL, percent improvement in Y-BOCS was converted to mean improved utility (Bystritsky et al, 1999; Thompson and Higgins, 2002; Volpato Cordioli et al, 2003; Sousa et al, 2006; Besiroglu et al, 2007; Norberg et al, 2008; Ross et al, 2008; Huppert et al, 2009; Hollander et al, 2010; Huff et al, 2010; Reddy et al, 2010; Simpson et al, 2010; Andersson et al, 2011; Srivastava et al, 2011; Farris et al, 2013; Ooms et al, 2014; Kumar et al, 2019). In addition, a subtree of incidence of each reported complication and its effect on utility was constructed to determine the utility of the average patient with postoperative complications or surgical side effects from RF capsulotomy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of Kumar et al comparing ABL and DBS in OCD concluded that ablative surgery has a higher overall utility than DBS, mostly because of the lower complication rate of ablative surgery. 19 However, several overlapping samples were included in the analysis, 5,[20][21][22][23][24][25][26][27] which could have led to a distorted estimation of the actual effectiveness. Furthermore, no formal meta-regression was performed to determine systematic differences in variance between studies on ABL or DBS concerning efficacy and adverse events.…”
Section: Introductionmentioning
confidence: 99%